2017
DOI: 10.1055/s-0043-120440
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Adiposity Index was a useful Predictor of Prediabetes

Abstract: VAI was positively associated with prediabetes, and also a usefulindicator of prediabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 37 publications
0
24
0
2
Order By: Relevance
“…[ 20 23 ] This showed that VAI is associated with poor glucose control, increased insulin resistance and impaired β-cell function. [ 24 26 ] VAI is associated not only with DM but also with increased cardiometabolic risk. [ 23 ] The multiple components of VAI (BMI, WC, TG, and HDL-C) have a stronger association with induced inflammation and adipocytokine production, which may explain the higher predictive power of VAI for DM, compared with BMI alone.…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 23 ] This showed that VAI is associated with poor glucose control, increased insulin resistance and impaired β-cell function. [ 24 26 ] VAI is associated not only with DM but also with increased cardiometabolic risk. [ 23 ] The multiple components of VAI (BMI, WC, TG, and HDL-C) have a stronger association with induced inflammation and adipocytokine production, which may explain the higher predictive power of VAI for DM, compared with BMI alone.…”
Section: Discussionmentioning
confidence: 99%
“…There were substantial researches exploring the associations of VAI with chronic diseases in human, which proved that VAI was negatively associated with insulin sensitivity [16,17] and identified as a powerful indicator for pre-diabetes or diabetes [18][19][20], and positively associated with the risk of hyperuricemia [21] and nonalcoholic fatty liver disease (NAFLD) [22]. Additionally, the results of several epidemiological studies [9,15,23] exploring the association between visceral adiposity and risk of hypertension showed that VAI was positively associated with the risk of hypertension in Chinese adult population [9] or Japanese Americans [24], and baseline scores of VAI could predict hypertension and CVD incident in prehypertension or healthy population [15,23], whereas others reported no association [25] or an association in women but not men [26].…”
Section: Introductionmentioning
confidence: 99%
“…Since VAI has been proposed as an indicator of adipose tissue dysfunction, there are some studies supported that VAI is a powerful indicator of hypertension, diabetes and hyperuricemia, but the study of relations between VAI and NAFLD is less. In our study, the results indicated that increased VAI levels was significantly and independently associated with the risk of developing NAFLD.…”
Section: Discussionmentioning
confidence: 99%